The Effectiveness of Academic Supervision of Principals in Improving Teachers' Pedagogic Competence - Wifqi Rahmi; Hendra Sidratul Aziz (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the effectiveness of school principals' academic supervision in improving teachers' pedagogical competence at Madrasah Aliyah Negeri 1 Jembrana. The research uses a descriptive qualitative approach with the research subjects including the principal, deputy principal for curriculum, school supervisors, and ten teachers. Data collection was carried out through classroom observations, in-depth interviews, and documentation of supervision tools and teacher learning tools. Data analysis was carried out using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that academic supervision has been carried out in a planned and systematic manner through the stages of planning, learning observation, evaluation, and follow-up. Supervision is also delivered through various forms, including class visits, learning administration checks, coaching, mentoring, and reflective discussions. Academic supervision has been proven to improve teachers' pedagogical competence, especially in learning planning, the variety of teaching methods, the use of learning media, classroom management, and more structured learning evaluation. Key supporting factors include open communication by principals, teacher motivation, collaborative school culture, and internal training. The obstacles found include limited time for school principals, psychological pressure on teachers, and supervision instruments that are not optimal. This study recommends academic supervision through continuous coaching to ensure consistent improvement in learning quality.